Police Deception: A Survey of EKU Students - Nicholson, Jason Anthony (2013)
Abstract Police deception has been both good and bad for society. Deceptive interrogation is an effective method of gaining confessions and convictions. It is also dangerous in that it raises the potential for false confessions, damages police-citizen relationships, damages case strength, and encourages lying in other aspects of policing. The purpose of the study was to gauge the opinions of students regarding deceptive interrogation by police. A survey was administered to a purposive sample of undergraduates at Eastern Kentucky University. The survey asked questions regarding the students' level of approval toward different scenarios of police deception. It also asked some general questions regarding the police and lying. The sample's average responses indicated negative to neutral feelings of police use of deception. In no circumstance did the sample's average responses approve of deception by police